1998
DOI: 10.1103/physrevd.57.1171
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariance and effective actions inD=3at finite temperature

Abstract: For background gauge field configurations reducible to the form Aµ = (Ã3, A( x)) whereÃ3 is a constant, we provide an elementary derivation of the recently obtained result for the exact induced Chern-Simons (CS) effective action in QED3 at finite temperature. The method allows us to extend the result in several useful ways: to obtain the analogous result for the 'mixed' CS term in the Dorey-Mavromatos model of parity-conserving planar superconductivity, thereby justifying their argument for flux quantization i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…This mechanism extends [7,8,9,10,11,12] to 2+1 dimensional Abelian theories for a restricted class of static backgrounds A µ = (A 0 (t), A( x)). However, this is not the full answer, since for these backgrounds (and for their trivial non-abelian generalizations) the "large" gauge transformations in fact have zero winding number -the shift in the Chern-Simons actions comes from a total derivative term, not from the winding number piece.…”
Section: Introductionmentioning
confidence: 74%
“…This mechanism extends [7,8,9,10,11,12] to 2+1 dimensional Abelian theories for a restricted class of static backgrounds A µ = (A 0 (t), A( x)). However, this is not the full answer, since for these backgrounds (and for their trivial non-abelian generalizations) the "large" gauge transformations in fact have zero winding number -the shift in the Chern-Simons actions comes from a total derivative term, not from the winding number piece.…”
Section: Introductionmentioning
confidence: 74%
“…On the other hand, Chern-Simons theory has induced many significative studies in QED 3 [15][16][17][18]. Besides introducing Chern-Simons term into the normal QED 3 Lagrangian, it was also found that in QED 3 with two-component fermions a Chern-Simons like term can also be induced from radiative corrections [19][20][21][22][23][24][25] (Appendix A). However, this result does not hold for QED 3 with four-component fermions due to the property of γ matrix algebra.…”
mentioning
confidence: 99%
“…Recent finite temperature studies [1][2][3][4][5][6][7][8] of 2+1 dimensional Chern-Simons systems [9] have revealed several interesting new features of induced parity violating terms at finite temperature. It is well known [10,11] that at T=0, for fermions in the presence of a static magnetic flux Φ = d 2 x eB 2π there is an induced charge…”
mentioning
confidence: 99%
“…where β = 1 T is the inverse temperature. The corresponding parity-odd part of the (Euclidean) finite temperature induced effective action is [1][2][3][4][5][6][7][8] S P −odd = −iΦ arctan tanh( βm 2 ) tan( 1 2 β 0 eA 0 dτ )…”
mentioning
confidence: 99%
See 1 more Smart Citation